ANALISIS ASPEK PASAR DAN PEMASARAN PENDIRIAN INDUSTRI DODOL SALAK SKALA KECIL DI KABUPATEN BANJARNEGARA - Agus Suprapto (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2013)
This research aims to analyze the feasibility of the market and marketing of industrial establishment Dodol salak. The method used in this study is the survey method and sampling technik is accidental sampling. The number of samples taken 112 people. The results of the market and marketing analysis showed that 84 respondents (74.11%) had knowledge of Dodol salak. Respondents who had knowledge of Dodol salak 71 people (84.52%) had been consumed. Respondents who stated like Dodol salak by 67 people (79.76%). Dodol salak is a product that is preferred by consumers. The market for this products is still wide open. Dodol salak market development can be done through the promotion and guarantee the availability of products on the market. Key words: dodol salak and market aspects